Lessons Learned from 30 Years of MINIX. - TANENBAUM, ANDREW S. (Communications of the ACM, 2016)
The article discusses the lessons learned from the development of the computer operating system called MINIX. Topics covered include how MINIX was created in 1984, how the author distributed the codes in developing MINIX, and the importance of determining how to market or distribute MINIX. It also discusses the different modes of the MINIX, how MINIX was made appropriate for hardware, and details relating to the porting system of MINIX.